From Human Resource Development to National Human Resource Development: resolving contemporary HRD challenges - Devadas, Udaya Mohan; Silong, Abu Daud; Krauss, Steven Eric; Ismail, Ismi Arif (Universiti Putra Malaysia Press, 2012)

(untitled)
Faced by past and present challenges, efforts have been made to extend the scope of Human Resource Development (HRD) to cover national level HRD issues with an emerging new paradigm of HRD research agenda, the National Human Resource Development (NHRD) as proposed by McLean and others in 2004. This paper provides a review of the literature related to HRD and NHRD, with the main purpose to critically debate the adequacy of HRD and the plausibility of NHRD in resolving contemporary HRD challenges. Through the review of related literature, a set of contemporary challenges were identified from the environment, as well as at the entry, task, validation and exit levels of HRD processes. The capability of HRD in resolving these challenges was critiqued, and it illuminated a distinction between traditional HRD (THRD) and modern HRD (MHRD). Based on the discussion, an emerging theoretical base of HRD was modelled, and the NHRD was proposed and highlighted to resolve contemporary challenges